2014
DOI: 10.1063/1.4868724
|View full text |Cite
|
Sign up to set email alerts
|

On the limits to Ti incorporation into Si using pulsed laser melting

Abstract: Fabrication of p-Si(111) layers with Ti levels well above the solid solubility limit was achieved via ion implantation of 15 keV 48Ti+ at doses of 1012 to 1016 cm−2 followed by pulsed laser melting using a Nd:YAG laser (FWHM = 6 ns) operating at 355 nm. All implanted layers were examined using cross-sectional transmission electron microscopy, and only the 1016 cm−2 Ti implant dose showed evidence of Ti clustering in a microstructure with a pattern of Ti-rich zones. The liquid phase diffusivity and diffusive ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…The degree of crystallization depends on the energy used during the PLM process, and the implanted layers are clearly better ordered as the energy grows. It has been argued [23] that the implanted element could remain trapped in defects or be accumulated unevenly due to the process known as cellular breakdown. As the carrier concentration remains almost constant (Table I), this effect in not determining, at least for the conductive properties of the films.…”
Section: Iv-discussionmentioning
confidence: 99%
“…The degree of crystallization depends on the energy used during the PLM process, and the implanted layers are clearly better ordered as the energy grows. It has been argued [23] that the implanted element could remain trapped in defects or be accumulated unevenly due to the process known as cellular breakdown. As the carrier concentration remains almost constant (Table I), this effect in not determining, at least for the conductive properties of the films.…”
Section: Iv-discussionmentioning
confidence: 99%
“…However, it is worth mentioning that the interface instability in form of a cellular breakdown 22 , 23 occurs when the Ti doping concentration reaches 1–2 × 10 21 cm −3 (2–4 at. %) during rapid solidification 24 . In a recent paper, we have also reported that the cellular breakdown takes place in Ti-implanted Si samples after pulsed laser annealing (PLA), but it can be effectively suppressed by millisecond-flash lamp annealing (FLA) 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Ti diffusion towards the surface after annealing, which is shown in figure 3. Solute concentration profile shows a spike due to the larger v D in the liquid at the solidification front 20 , which is caused by dramatically solute partitioning at the liquid-solid interface. This spike increases the chance of cellular breakdown, the morphologically instability happens at the liquid-solid interface, resulting in the lateral segregation of Ti impurities and leading to a cellular breakdown microstructure in figure 4 (a).…”
Section: The Impurity Incorporation Of Ti Implanted Si Was Interpretementioning
confidence: 99%
“…reported that Ti ions massively occupy interstitial sites in the host semiconductor in highly Ti- 20 . This is attributed to the fact that during pulsed laser annealing and rapid solidification the impurities diffuse to the surface of the implanted layer and form a cellular breakdown microstructure, preventing further recrystallization 20 .…”
Section: Introductionmentioning
confidence: 99%